Paleoclimatic evidence in duricrust, paleosoils and siliciclastic deposit of the Cenozonic of Uruguay - Tófalo, O.R. (2009)
The continental deposits found in southern and western Uruguay show important climatic changes along the Cenozoic. The sequence begins with Paleocene palustrine carbonates known as the Queguay Formation, associated with calcretes of phreatic origin which developed mainly on fluvial sediments of Mercedes Formation (Late Cretaceous), and indicates a semiarid climate, seasonally contrasted. The Asencio Formation (Early Eocene) is separated from Mercedes Formation by the Yapeyu paleosurface, limiting two sedimentary cycles. Fluvial deposits lies above this surface, on which Ultisols developed under a warm and humid climate; periods of intense dryness would provoked their induration and formation of ferricretes, which under subsequent increased precipitation were dismantled. Above, Fray Bentos Formation (Oligocene-Early Miocene) lies unconformably. It is composed by loessic sediments deposited in a semiarid climate, paleosols and diverse pedogenic calcretes developed on these sediments, among which a new type named tubular calcrete, are here described; in the latter the tubular units are related to a coarse prismatic structure derived from shrink-swell processes and the surface morphology of this calcrete refers to a gilgai microrelief, typical for Vertisols. The pedogenic calcretes point to a seasonal semiarid climate. The Raigón Formation (Late Pliocene- Middle Pleistocene) of fluvial origin was formed in a humid period, and shows a paleosol at the top developed in a seasonally contrasted climate. Lying unconformably, the Libertad Formation (Early to Middle Pleistocene) is composed by loesses deposited during glacial periods that were subsequently modified by pedogenesis during interglacial periods.